(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: The most prevalent arrhythmia is atrial fibrillation (AF) and in this case, symptomatic relief may involve rate control. Metoprolol may be applied intravenously and verapamil is used in the treatment of rate control of acute AF. Their relative efficacy and safety are critical to understand so that management strategies could be chosen depending on the specifics of the patients. Objective: To determine the comparative efficacy, safety and rate to control of intravenous metoprolol with intravenous verapamil in patients with atrial fibrillation in an acute care facility. Study design: A prospective study. Place and Duration of study: From 01 July 2024 to 31 December 2024 Cardiology Department Sandeman Provincial Hospital / Bolan Medical Complex Hospital Quetta. Methods: It was a prospective study at one tertiary hospital. Acute AF patients in need of rate control were randomly given either intravenous metoprolol or verapamil. Heart rate control, adverse events and time to reach target heart rate (≤ 100 bpm) were evaluated at 30, 60 and 90 minutes after administration. Paired t-tests and chi-square comparisons were used in the statistical analysis of efficacy and safety. Results: 100 patients (mean age 62.4 ± 10.3 years) were used. The achievement of target heart rate (≤ 100 bpm) was reached in 45 minutes in the metoprolol group, and in 30 minutes in verapamil group. The drugs had the same effect on rate control (p = 0.75) though verapamil was found to have a better onset of action (p < 0.05). The verapamil group reported adverse events that were more frequent (20% vs. 8%, p = 0.03), the most frequent being hypotension and bradycardia. Conclusion: Intravenous metoprolol and verapamil are both effective in the rate control of acute atrial fibrillation. Verapamil is faster acting but metoprolol can be a safer profile, especially in patients having underlying heart disease. Selection between the two agents must be based on patient specific features, such as comorbidities and pre-disposition to adverse events.